A heavy rare earth-free grain boundary diffusion magnet and a preparation method thereof

CN122907461APending Publication Date: 2026-10-13HANGZHOU MAGMAX TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611381600.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]为了解决在不含重稀土情况下,在扩散磁体中促进形成稳定的NdFeGa相,以及提高无重稀土磁体的内禀矫顽力的问题,本申请提供一种无重稀土晶界扩散磁体及其制备方法

Benefits of technology

本申请针对Ga含量不小于0.2wt%的无重稀土磁体基体采用依次覆第一扩散层、第二扩散层的方式,且对第二扩散层的材料、第二扩散层的材料分别进行了限定。第一扩散层的材料为TiXCu1-X合金,熔融后,可有效增加扩散深度,扩散后表面形成TiB相,促进无重稀土磁体基体内部Nd6Fe13Ga相的形成,从而提升扩散深度,并且提高HcJ。第二扩散层的材料为PrxAlyCozCu1-x-y-z合金,熔点低,相比对重稀土扩散可以在更低的温度下形成液相。Pr元素扩散后进入会与Nd元素进行置换,在主相晶粒表层形成PrFeB壳层,PrFeB各项异性场要强于NdFeB,从而提高HcJ。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907461A_ABST
    Figure CN122907461A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of heavy rare earth-free neodymium-iron-boron magnets, and particularly discloses a heavy rare earth-free grain boundary diffusion magnet and a preparation method thereof. The heavy rare earth-free grain boundary diffusion magnet comprises a heavy rare earth-free magnet substrate, a first diffusion layer sequentially covering the outer surface of the heavy rare earth-free magnet substrate from inside to outside, and a second diffusion layer covering the outer surface of the first diffusion layer; the Ga content of the heavy rare earth-free magnet substrate is not less than 0.2 wt%; the material of the first diffusion layer is Ti X Cu 1‑X ; the material of the second diffusion layer is Pr x Al y Co z Cu 1‑x‑y‑z ; in the material of the first diffusion layer, X=20at%-40at%; in the material of the second diffusion layer, x=70wt%-90wt%, y=0-9wt%, and z=0-10wt%. The application adopts the mode of sequentially covering the first diffusion layer and the second diffusion layer for the heavy rare earth-free magnet substrate with the Ga content not less than 0.2 wt%, and limits the material of the second diffusion layer and the material of the second diffusion layer, which is beneficial to improving the diffusion depth and HcJ.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of heavy rare earth-free neodymium iron boron magnet technology, and more specifically, it relates to a heavy rare earth-free grain boundary diffusion magnet and its preparation method. Background Technology

[0002] With the development of industries such as new energy vehicles and intelligent vehicles, sintered NdFeB has become a key functional material driving the rapid development of emerging industries and a crucial support for the intelligent, miniaturized, and lightweight development of related fields. However, due to the scarcity and high price of heavy rare earth elements Dy and Tb, the preparation cost of NdFeB magnets has increased dramatically, resulting in expensive magnets. Therefore, the preparation of heavy rare earth-free sintered NdFeB magnets has become the direction of industrial development.

[0003] Grain boundary diffusion technology represents a significant technological innovation for NdFeB magnets and the entire permanent magnet industry in the 21st century. Through grain boundary diffusion, high coercivity and high energy product can be achieved, while also enabling the manufacture of high-performance magnets with low or no heavy rare earth elements. Currently, industrial production tends to use heavy rare earth fluorides and pure heavy rare earth elements for grain boundary diffusion. For magnets without heavy rare earth elements (such as light rare earth elements and light rare earth alloys), grain boundary diffusion technology is less commonly used, mainly because light rare earth diffusion often results in low HcJ improvement and unstable performance. Therefore, developing stable heavy rare earth-free magnets using grain boundary diffusion technology is crucial.

[0004] Currently, high HcJ-free rare-earth magnets are typically prepared using a high gallium, low boron elemental composition, i.e., increasing the proportion of Ga and decreasing the proportion of B. However, the NdFeGa phase in heavy rare-earth-free magnets is unstable, resulting in significant performance fluctuations. Meanwhile, conventionally powder-metallurgical magnets, with a (PrNd)FeB magnetocrystalline anisotropy field of only 5600 kA / m (less than half that of DyFeB and only one-third that of TbFeB), present significant challenges. Therefore, promoting the formation of a stable NdFeGa phase in diffused magnets without heavy rare-earth elements and improving the HcJ of heavy rare-earth-free magnets remain major problems that need to be addressed. Summary of the Invention

[0005] To address the challenges of promoting the formation of a stable NdFeGa phase in a diffusion magnet without heavy rare earth elements, and to improving the intrinsic coercivity of heavy rare earth-free magnets, this application provides a heavy rare earth-free grain boundary diffusion magnet and its preparation method.

[0006] Firstly, this application provides the following technical solution: A rare-earth-free grain boundary diffusion magnet includes a rare-earth-free magnet matrix, a first diffusion layer sequentially covering the outer surface of the rare-earth-free magnet matrix from the inside out, and a second diffusion layer covering the outer surface of the first diffusion layer; the Ga content of the rare-earth-free magnet matrix is ​​not less than 0.2 wt%. The material of the first diffusion layer is Ti X Cu 1-X The material of the second diffusion layer is Pr. x Al y Co z Cu 1-x-y-z ; In the material of the first diffusion layer, X = 20 at% - 40 at% In the material of the second diffusion layer, x = 70wt%-90wt%, y = 0-9wt%, and z = 0-10wt%.

[0007] This application focuses on magnets without heavy rare earth elements as a substrate, investigating how to improve HcJ and performance stability on such heavy rare earth-free magnet substrates. The heavy rare earth-free magnet substrate used in this application is prepared through conventional powder metallurgy steps and does not contain heavy rare earth elements such as Gd, Tb, and Dy, but contains at least 0.2 wt% Ga.

[0008] In this application, a first diffusion layer and a second diffusion layer are sequentially coated on a heavy rare earth magnet substrate.

[0009] The material of the first diffusion layer is Ti. X Cu 1-X The alloy, after melting, can effectively increase the diffusion depth, and a TiB phase forms on the surface after diffusion, promoting the formation of Nd6Fe within the heavy rare earth magnet matrix. 13 The formation of the Ga phase increases HcJ. According to the Cu-Nd phase diagram, when the Cu content is between 0% and 30%, as the Cu content increases, Cu elements enter the grain boundary phase, lowering the melting point of the Cu-Nd alloy and making the Nd-rich phase easier to melt, thereby increasing the diffusion depth.

[0010] Meanwhile, Ti and B have a very strong thermodynamic affinity. Due to the extremely low diffusion rate of Ti, the Ti concentration on the surface is extremely high in localized areas. Driven by high temperatures, the B-rich phase on the surface and near the surface reacts with Ti to form a stable and high-melting-point substance, TiB2, which consumes the B content and thus promotes the Nd6Fe2+ reaction. 13 Ga phase is formed; at the same time, Ti element has the effect of inhibiting the growth of main phase grains, thereby optimizing the distribution of grain boundary phase.

[0011] The material of the second diffusion layer is Pr. x Al y Coz Cu 1-x-y-z As a low-melting-point alloy, it can form a liquid phase at a lower temperature compared to the diffusion of heavy rare earth elements. After diffusion, Pr elements will substitute with Nd elements, forming a PrFeB shell on the surface of the main phase grains. The anisotropic field of PrFeB is stronger than that of NdFeB, thus improving HcJ. Al elements can improve the wettability between the Nd-rich phase and the main solid phase, making the grain boundary phase distribution more uniform, thereby improving HcJ.

[0012] The method in this application is applicable to diffusion in any sintered NdFeB magnet with a Ga content of not less than 0.2 wt%.

[0013] Furthermore, in the material of the first diffusion layer, X = 20at%-30at; in the material of the second diffusion layer, x = 80wt%-90wt%, y = 0-5wt%, z = 0-6wt%.

[0014] When the materials of the first diffusion layer and the second diffusion layer are selected within the above range, HcJ can be further improved.

[0015] Secondly, this application provides the following technical solution: A method for preparing a heavy rare earth grain boundary diffusion magnet includes the following steps: Step 1: Cover the surface of the heavy rare earth magnet substrate with the material of the first diffusion layer, the weight gain of the covering is 0.1~0.5wt% of the heavy rare earth magnet substrate, and obtain magnet 1 covered with the first diffusion layer; Step 2: Cover the outer surface of magnet 1 with the material of the second diffusion layer, the weight gain of the covering is 0.5~5.0wt% of the weightless rare earth magnet matrix, to obtain magnet 2 covered with the second diffusion layer; Step 3: Perform grain boundary diffusion treatment on magnet 2. The grain boundary diffusion temperature is 700-1000℃ and the treatment time is 3.5-16.5h; the tempering temperature is 400-600℃ and the time is 3-6h to obtain a heavy rare earth-free grain boundary diffused magnet.

[0016] In order to better control the weight gain of the first and second diffusion layers, in step one, the weight gain of the first diffusion layer is 0.5~5.0 wt% of the weightless rare earth magnet matrix; in step two, the weight gain of the second diffusion layer is 0.5~5.0 wt% of the weightless rare earth magnet matrix. The increase in HcJ is controlled by adjusting the weight gain.

[0017] Ti used in the diffusion source X Cu 1-xThe melting point of the (40≥x≥20) alloy is (864℃~942℃), therefore the initial temperature is 850~1000℃. The purpose is to melt TiCu, allowing Cu to enter the grain boundary phase and lower the melting point of the Cu-Nd alloy. Trace amounts of Ti can promote the Nd6Fe alloy. 13 Ga phase formation inhibits the growth of main phase grains and thus optimizes the distribution of grain boundary phases.

[0018] A Ti layer is formed on the surface of the obtained heavy rare earth grain boundary diffusion magnet. x B 1-x The alloy strip (60≥x≥85) has a Ga content of more than 0.5wt% at any point of the grain boundary phase, with an average of more than 1.0wt%. The light rare earth diffusion depth is more than 2.0mm, and the HcJ increase can be precisely controlled between 0.5~5kOe according to the weight gain of the diffusion source, as well as the diffusion temperature and diffusion time.

[0019] Furthermore, in step three, the grain boundary diffusion treatment is divided into two stages: the first stage diffusion temperature is 850~1000℃ and the first stage diffusion time is 0.5~1.5h; the second stage diffusion temperature is 700~950℃ and the second stage diffusion time is 3~15h.

[0020] In this application, the grain boundary diffusion process is divided into two stages, and the temperature of the first stage diffusion is higher than that of the second stage diffusion, but the diffusion time of the first stage diffusion is shorter than that of the second stage diffusion.

[0021] Furthermore, in step two, the weight gain of the covering is between 0.5wt and 2.0wt, the second-stage diffusion temperature is between 800 and 950℃, and the second-stage diffusion time is between 3 and 8 hours.

[0022] Furthermore, in step two, the weight gain of the covering is 2.0wt~4.0wt%, the second-stage diffusion temperature is 700~900℃, and the second-stage diffusion time is 6~15h.

[0023] Furthermore, in step two, the weight gain of the coating is 4.0wt%~5.0wt%, the first-stage diffusion temperature is 900~950℃, and the first-stage diffusion time is 0.5~1.5h; the second-stage diffusion temperature is 700~850℃, and the second-stage diffusion time is 12~15h.

[0024] The mechanism of the diffusion source involved in this application is as follows: After diffusion, Pr elements substitute with Nd elements to form a PrFeB shell on the surface of the main phase grains. The anisotropic field of PrFeB is stronger than that of NdFeB, thus improving HcJ. Simultaneously, the diffusion of NdFeB in the main phase partially dissolves, promoting continuous and uniform thickening of the grain boundary phase and reducing magnetic exchange coupling between adjacent main phase grains, thereby enhancing HcJ. Controlling the diffusion time and weight gain aims to increase the amount of TiB formed, reduce the B content inside the magnet, and thus promote the formation of (PrNd)6Fe13Ga. The extended diffusion time also allows for more complete melting of the Nd-rich phase, facilitating the penetration of the diffusion source along the grain boundary phase into the interior, thereby increasing the diffusion depth.

[0025] When the coverage weight gain and diffusion parameters in step two are 0.5wt%~2.0wt%, the second-stage diffusion temperature is 800~950℃, and the second-stage diffusion time is 3~8h, the increase in HcJ is 0.5~2kOe.

[0026] When the cover weight gain and diffusion parameters in step two are 2.0wt%~4.0wt%, the second-stage diffusion temperature is 700~900℃, and the second-stage diffusion time is 6~15h, the increase in HcJ is 2~4kOe.

[0027] When the cover weight gain and diffusion parameters in step two are: cover weight gain of 4.0wt%~5.0wt%, first-stage diffusion temperature of 900~950℃, first-stage diffusion time of 0.5~1.5h; second-stage diffusion temperature of 700~850℃, second-stage diffusion time of 12~15h, the increase in HcJ is 4~5kOe.

[0028] Furthermore, in steps one and two, the method for covering the material of the first diffusion layer and the method for covering the material of the second diffusion layer are one of coating, magnetron sputtering, spraying, and screen printing.

[0029] In this application, the method of coating the first diffusion layer with the material and the method of coating the second diffusion layer with the material can be the same, but it is necessary to coat the first diffusion layer with the material and make it into a layer before coating the second diffusion layer with the material to form the second diffusion layer.

[0030] Furthermore, in steps one and two, the covering method is screen printing, and the material of the first diffusion layer or the material of the second diffusion layer consists of the following percentage components: Solvent 18-20wt; first or second diffusion source powder 80wt; resin 0-2wt.

[0031] When screen printing is used in this application, the first diffusion source powder, solvent, and resin are mixed in a specific ratio to form the material of the first diffusion layer, and the second diffusion source powder, solvent, and resin are mixed in a specific ratio to form the material of the second diffusion layer, and then screen printing is performed, which is beneficial to improve the coverage of the material of the first diffusion layer and / or the material of the second diffusion layer.

[0032] In summary, this application has the following beneficial effects: This application describes a method for sequentially coating a first diffusion layer and a second diffusion layer onto a heavy rare-earth magnet substrate with a Ga content of not less than 0.2 wt%, and specifies the materials of the second diffusion layer and the material of the second diffusion layer. The material of the first diffusion layer is Ti. X Cu 1-X The alloy, after melting, can effectively increase the diffusion depth, and a TiB phase forms on the surface after diffusion, promoting the formation of Nd6Fe within the heavy rare earth magnet matrix. 13 The formation of the Ga phase increases the diffusion depth and improves HcJ. The material of the second diffusion layer is Pr. x Al y Co z Cu 1-x-y-z The alloy has a low melting point and can form a liquid phase at a lower temperature compared to the diffusion of heavy rare earth elements. After diffusion, Pr elements will substitute with Nd elements to form a PrFeB shell on the surface of the main phase grains. The anisotropic field of PrFeB is stronger than that of NdFeB, thereby improving HcJ.

[0033] In this application, the weight gain of the first diffusion layer and the second diffusion layer is also limited, as are the diffusion temperature and diffusion time, which helps to achieve a more ideal increase in HcJ. Attached Figure Description

[0034] Figure 1 This is the Ti-Cu phase diagram.

[0035] Figure 2 These are SEM images of each region in Examples 1-6 of this application.

[0036] Figure 3 Surface SEM analysis of Examples 1-6 in this application.

[0037] Figure 4 SEM images of each region in Examples 1-1 of this application.

[0038] Figure 5 SEM images of each region in Comparative Example 1-1 of this application.

[0039] Figure 6 Surface Ti element distribution diagrams of Examples 2-3 in this application. Detailed Implementation Example

[0040] Example 1-1: A heavy rare earth-free grain boundary diffusion magnet. A heavy rare earth-free magnet substrate, N45H, is selected and prepared using conventional powder metallurgy. The substrate is cut into 2.25mm thick pieces, and a diffusion source is printed onto the product surface. The product is then placed in a vacuum sintering furnace for diffusion. The specific steps are as follows: Preparation of heavy rare earth-free magnet matrix N45H: The magnet is composed of RT-M1-M2-B, wherein R is Pr and Nd accounting for 31.8wt%, M1 is Al and Cu accounting for 0.40wt% and 0.33wt% respectively, M2 is Co, Ga and Zr accounting for 1.5%, 0.55wt% and 0.15wt% respectively, B is boron accounting for 0.89wt%, and the remainder is Fe. It is prepared by a series of conventional powder metallurgy processes of melting-crushing-air jet milling-pressing and sintering. A thin sheet with a thickness of 2.25mm is obtained by wire cutting and ultrasonic cleaning.

[0041] Step 1: Printing the diffusion source: A PrAlCu alloy paste is screen-printed onto a thin film. The alloy contains 82wt%, 6wt%, and 12wt% of the three elements, respectively. The paste is prepared from 80wt% PrAlCu powder, 20wt% terpineol, and 0.8wt% PVB. After drying, the printed alloy paste has a weight gain of 2.2wt% of the heavy rare-earth-free magnet matrix. The magnet is then placed in a vacuum sintering furnace for diffusion at 800℃ for 8 hours, followed by aging at 500℃ for 4 hours, resulting in a heavy rare-earth-free grain boundary diffused magnet.

[0042] Step 2: The heavy rare earth-free grain boundary diffusion magnet is cut into 7*6*2.25 mm pieces. After the surface oxide layer is polished with sandpaper, the magnetic properties are tested at 20℃±0.1℃ on PFM. The microstructure and micro-composition are analyzed using SEM and EPMA.

[0043] Examples 1-2 describe a heavy rare earth-free grain boundary diffusion magnet. A heavy rare earth-free magnet substrate, N45H, is selected and prepared using conventional powder metallurgy. The substrate is cut into 2.25mm thick pieces, and a diffusion source is printed onto the product surface. The product is then placed in a vacuum sintering furnace for diffusion. The specific steps are as follows: Preparation of N45H magnet matrix without heavy rare earth elements: The magnet is composed of RT-M1-M2-B, wherein R is Pr and Nd accounting for 31.8wt%, M1 is Al and Cu accounting for 0.40wt% and 0.33wt% respectively, M2 is Co, Ga and Zr accounting for 1.5wt%, 0.55wt% and 0.15wt% respectively, B is boron accounting for 0.89wt%, and the remainder is Fe. It is prepared by a series of conventional powder metallurgy processes of melting-crushing-air jet milling-pressing and sintering. A thin sheet with a thickness of 2.25mm is obtained by wire cutting and ultrasonic cleaning.

[0044] Step 1: Printing the diffusion source: First, print the first diffusion layer. The material of the first diffusion layer is TiCu slurry, in which the proportions of Ti and Cu are 40 at% and 60 at% respectively. After printing and drying, the first diffusion layer has a weight gain of 0.5 wt% compared to the heavy rare earth magnet substrate. Step two: A second diffusion layer is printed on the outer surface of the first diffusion layer. The material of the second diffusion layer is a PrAlCu alloy paste, in which the proportions of the three elements are 82wt%, 6wt%, and 12wt%, respectively. The paste is prepared from 80wt% PrAlCu powder, 20wt% terpineol, and 0.8wt% PVB. After drying, the printed second diffusion layer has a weight gain of 2.2wt% of the heavy rare earth-free magnet matrix. The magnet is then placed in a vacuum sintering furnace for diffusion at 800℃ for 8 hours, and simultaneously aged at 500℃ for 4 hours to obtain a heavy rare earth-free grain boundary diffused magnet.

[0045] Step 3: Cut the heavy rare earth grain boundary diffusion magnet into 7*6*2.25 mm pieces, polish the surface oxide layer with sandpaper, and then perform magnetic performance testing at 20℃±0.1℃ on PFM. Microstructure and micro-composition analysis are performed using SEM and EPMA.

[0046] Examples 1-3 describe a grain boundary diffusion magnet without heavy rare earth elements. The preparation method is the same as that of Examples 1-2, except that in step one, the material of the first diffusion layer is TiCu slurry, wherein the proportions of Ti and Cu are 30 at% and 70 at% respectively. After printing and drying, the first diffusion layer increases in weight to 0.5 wt% of the substrate without heavy rare earth elements.

[0047] Examples 1-4 describe a grain boundary diffusion magnet without heavy rare earth elements. The preparation method is the same as that of Examples 1-2, except that in step one, the material of the first diffusion layer is TiCu slurry, wherein the proportions of Ti and Cu are 20at and 80at, respectively. After printing and drying, the first diffusion layer increases in weight to 0.5wt% of the substrate without heavy rare earth elements.

[0048] Examples 1-5 describe a heavy rare earth grain boundary diffusion magnet prepared in the same way as in Examples 1-4, except that the diffusion in step two is divided into two stages: the first stage diffusion temperature is 850℃ and the first stage diffusion time is 0.5h, and the second stage diffusion temperature is 800℃ and the second stage diffusion time is 8h.

[0049] Examples 1-6 describe a heavy rare earth grain boundary diffusion magnet, prepared using the same method as Examples 1-5, except that the diffusion in step two is divided into two stages, with the first stage diffusion temperature at 902℃ and the first stage diffusion time at 1.0h.

[0050] Examples 1-7 describe a heavy rare earth grain boundary diffusion magnet, prepared using the same method as Examples 1-5, except that the diffusion in step two is divided into two stages, with the first stage diffusion temperature being 1000℃ and the first stage diffusion time being 1.5h.

[0051] Comparative Example Comparative Example 1-1: A heavy rare earth grain boundary diffusion magnet, which differs from Example 1-1 in that the operation steps in step one are not used.

[0052] Comparative Example 1-2: A heavy rare earth grain boundary diffusion magnet, which differs from Example 1-2 in that the operation steps in Step 1 and Step 2 are not used.

[0053] The residual magnetism and intrinsic coercivity of the embodiments and comparative examples in this application were tested, and the data were recorded and analyzed.

[0054] Table 1. Remanence and intrinsic coercivity of Example Group 1 and Comparative Examples 1-2

[0055] In Table 1, the magnetic flux Br represents the effective magnetic flux output capability of the grain boundary diffusion magnet without heavy rare earth elements. A higher value indicates a greater magnetic induction intensity of the magnet. The intrinsic coercivity HcJ represents the demagnetization resistance and temperature stability of the grain boundary diffusion magnet without heavy rare earth elements. A higher value indicates that the magnet is less prone to irreversible demagnetization under high temperature and reverse external field conditions, resulting in better reliability.

[0056] As shown in Table 1, although the remanence of the embodiment is slightly lower than that of the comparative example, the intrinsic coercivity of the embodiment is higher than that of the comparative example. Therefore, the embodiment has higher stability and high temperature resistance, and is more suitable for fields with higher reliability requirements such as motors, high temperature components, and precision measuring devices.

[0057] Parallel comparative examples 1-1, 1-2, 1-3, and 1-4 show that first coating a first diffusion layer (the material of the first diffusion layer is TiCu alloy) and then coating a second diffusion layer (the material of the second diffusion layer is PrAlCu alloy) can effectively improve the intrinsic coercivity of the heavy rare earth grain boundary diffusion magnet.

[0058] Based on parallel comparative examples 1-4, 1-5, and 1-6, and in conjunction with Figure 1 The TiCu phase diagram yields the following conclusions: When Ti:Cu = 2:8, the melting point is 902℃. Therefore, according to the scheme of this application, the diffusion is divided into two stages. The temperature of the first stage is above the melting point of TiCu, which can effectively improve the HcJ after diffusion.

[0059] When the diffusion temperature is 800℃, the closer the melting point of TiCu alloys with different atomic percentages is to the diffusion temperature, the greater the increase in HcJ. The reason for this phenomenon is that the closer the diffusion temperature is to the melting point of TiCu, the more TiCu alloy melts, which is conducive to the diffusion of PrAlCu; conversely, if less TiCu alloy melts, it will hinder the diffusion of PrAlCu.

[0060] Based on the data from Examples 1-7 in Table 1, it can be concluded that excessively high diffusion temperature actually leads to a decrease in HcJ increase. It is speculated that the reason for this phenomenon is that excessively high temperature leads to an increase in grain diffusion rate, and a large amount of light rare earth alloy enters the main phase, causing the main phase to be destroyed.

[0061] Depend on Figure 2 , Figure 3 As shown in Table 2, after TiCu pre-diffusion and diffusion at high temperatures above 900℃, Ti will form a stable high-melting-point substance Ti with B. x B 1-x Alloy strips (60wt%≥x≥85wt%) can effectively consume the B element inside the magnet.

[0062] Table 2 shows the proportion of each element at two different locations in the surface SEM analysis of Examples 1-6.

[0063] Table 3. Proportion of each element at different positions in Examples 1-1, 1-6, and Comparative Example 1-1

[0064] Combination Figure 2 , Figure 4 , Figure 5Comparing Tables 2 and 3, the Pr content of the pre-printed TiCu alloy magnet is still more than 0.5wt% higher than the normal Pr content at a depth of 1.2mm. The diffusion depth of the product with only PrAlCu diffusion is 0.6mm. TiCu alloy pre-diffusion can improve the diffusion depth, thereby allowing Pr to replace Nd to form more PrFeB phase and improve HcJ.

[0065] A large amount of NdFeGa phase exists in the grain boundary phase, and the Ga content at any point exceeds 1.0 wt%, as detailed in Table 4.

[0066] Table 4. EDS analysis of magnets at 8 different locations in Examples 1-6

[0067] Example 2-1: A heavy rare earth-free grain boundary diffusion magnet, prepared in the same way as in Examples 1-6, except that in step one, the first diffusion layer (the raw material of the first diffusion layer is TiCu slurry) gains weight to 0.1 wt% of the heavy rare earth-free magnet matrix after printing and drying.

[0068] Example 2-2, a heavy rare earth-free grain boundary diffusion magnet, is prepared in the same way as in Examples 1-6, except that in step one, the first diffusion layer (the raw material of the first diffusion layer is TiCu slurry) increases in weight to 0.3wt% of the heavy rare earth-free magnet matrix after printing and drying.

[0069] Examples 2-3 describe a heavy rare earth-free grain boundary diffusion magnet prepared using the same method as Examples 1-6, except that in step one, the first diffusion layer (the raw material for the first diffusion layer is TiCu slurry) gains weight to 0.7 wt% of the heavy rare earth-free magnet matrix after printing and drying.

[0070] Examples 2-4 describe a heavy rare earth grain boundary diffusion magnet, prepared using the same method as Examples 1-6, except that in step one, the first diffusion layer (the raw material for the first diffusion layer is TiCu slurry) gains weight to 0.9 wt% of the heavy rare earth magnet matrix after printing and drying.

[0071] Table 5. Remanence and intrinsic coercivity of Examples 2-1 to 2-4

[0072] Combination Figure 3 and Figure 6 As can be seen, the bright areas represent the distribution of Ti elements, indicating that Ti elements are distributed on the surface of the magnet and basically do not enter the interior of the magnet.

[0073] Based on the comparative examples 1-6 and examples 2-1 to 2-4, and in conjunction with Table 5 and... Figure 6 The following conclusions can be drawn: With the TiCu alloy ratio ranging from 0.1 to 0.9 wt%, HcJ first increases and then decreases. The reason for this is likely that when the TiCu alloy ratio exceeds 0.7 wt%, a thin film of Ti alloy forms on the surface, which hinders the diffusion of PrAlCu. Therefore, the optimal TiCu element ratio is between 0.1 and 0.5 wt%.

[0074] Example 3-1: A heavy rare earth grain boundary diffusion magnet, prepared in the same way as in Examples 1-6, except that in the material of the second diffusion layer, PrNd accounts for 30 wt%, Al and Cu account for 0.5 wt% and 0.1 wt% respectively, Co and Ga account for 0.5 wt% and 0.20 wt% respectively, B content accounts for 0.95 wt%, and the balance is Fe.

[0075] Example 3-2, a heavy rare earth grain boundary diffusion magnet, is prepared in the same way as in Example 3-1, except that the material of the second diffusion layer is PrAlCo, wherein Pr accounts for 90wt%, Al accounts for 5wt%, and Co accounts for 5wt%.

[0076] Example 3-3: A heavy rare earth grain boundary diffusion magnet, prepared in the same way as in Example 3-1, except that the material of the second diffusion layer is PrCuCo, wherein Pr accounts for 89wt%, Cu accounts for 5wt%, and Co accounts for 6wt%.

[0077] Table 6. Performance of Heavy Rare Earth-Free Magnet Matrix Before and After Diffusion in Examples 3-1 to 3-3

[0078] As shown in Table 6, compared with the heavy rare earth magnet matrix, Examples 3-1 to 3-3 can all improve the intrinsic coercivity, among which PrAlCu is the best diffusion source.

[0079] Example 4-1: A grain boundary diffusion magnet without heavy rare earth elements is prepared in the same way as in Example 3-1, except that the material PrAlCu used for printing the second diffusion layer gains 3.9 wt% of the weight of the substrate after drying, the second diffusion temperature is 700℃, and the diffusion time is 10 h.

[0080] Example 4-2, a heavy rare earth-free grain boundary diffusion magnet, is prepared in the same way as in Example 4-1, except that the two-stage diffusion temperature is 750℃.

[0081] Example 4-3: A grain boundary diffusion magnet without heavy rare earth elements, prepared in the same way as in Example 4-1, except that the second-stage diffusion temperature is 800℃.

[0082] Example 4-4: A grain boundary diffusion magnet without heavy rare earth elements, prepared in the same way as in Example 4-1, except that the two-stage diffusion temperature is 850℃.

[0083] Examples 4-5 describe a heavy rare earth-free grain boundary diffusion magnet, prepared using the same method as in Example 4-1, except that the two-stage diffusion temperature is 900℃.

[0084] Examples 4-6 describe a heavy rare earth grain boundary diffusion magnet prepared using the same method as in Example 4-1, except that the two-stage diffusion temperature is 950°C.

[0085] Table 7. Performance of Heavy Rare Earth-Free Magnet Matrix Before and After Diffusion in Examples 4-1 to 4-5

[0086] As shown in Table 7, when comparing the performance of Examples 4-1 to 4-6 and the heavy rare earth magnet matrix, the HcJ increase is relatively large when the diffusion temperature is between 700 and 850℃. This is because the PrAlCu alloy has a low melting point (around 435℃). Temperatures above 850℃ will cause the diffusion source to melt prematurely and diffuse into the main phase, thereby destroying the main phase structure and resulting in a low HcJ increase.

[0087] Example 5-1: A grain boundary diffusion magnet without heavy rare earth elements, prepared in the same way as in Example 4-3, except that the material of the second diffusion layer is PrAlCu, and the weight gain after drying is 0.5wt% of the matrix of the magnet without heavy rare earth elements. The second-stage diffusion temperature is 800℃ and the second-stage diffusion time is 3h.

[0088] Example 5-2: A grain boundary diffusion magnet without heavy rare earth elements, prepared in the same way as in Example 5-1, except that the material of the second diffusion layer is PrAlCu, and the weight gain after drying is 1.0 wt% of the matrix of the magnet without heavy rare earth elements. The second-stage diffusion temperature is 800℃ and the second-stage diffusion time is 8h.

[0089] Example 5-3: A heavy rare earth-free grain boundary diffusion magnet, prepared in the same way as in Example 5-1, except that the material of the second diffusion layer is PrAlCu, and the weight gain after drying is 2.0 wt% of the weight gain of the heavy rare earth-free magnet matrix. The second-stage diffusion temperature is 800℃ and the second-stage diffusion time is 6h.

[0090] Example 5-4: A heavy rare earth grain boundary diffusion magnet, prepared in the same way as in Example 5-3, except that the material of the second diffusion layer is PrAlCu, the second-stage diffusion temperature is 950℃, and the second-stage diffusion time is 6h.

[0091] Example 5-5: A heavy rare earth grain boundary diffusion magnet, prepared in the same way as in Example 5-3, except that the material of the second diffusion layer is PrAlCu, the second-stage diffusion temperature is 700℃, and the second-stage diffusion time is 6h.

[0092] Examples 5-6 describe a heavy rare earth-free grain boundary diffusion magnet prepared using the same method as in Example 5-1, except that the material of the second diffusion layer is PrAlCu, and the weight gain after drying is 2.5 wt% of the heavy rare earth-free magnet matrix. The second-stage diffusion temperature is 800℃, and the second-stage diffusion time is 8h.

[0093] Examples 5-7 describe a heavy rare earth-free grain boundary diffusion magnet prepared using the same method as in Example 5-1, except that the material of the second diffusion layer is PrAlCu, and the weight gain after drying is 4.0 wt% of the heavy rare earth-free magnet matrix. The second-stage diffusion temperature is 800℃, and the second-stage diffusion time is 15 h.

[0094] Examples 5-8 describe a heavy rare earth-free grain boundary diffusion magnet prepared using the same method as in Example 5-1, except that the material of the second diffusion layer is PrAlCu, and the weight gain after drying is 4.0 wt% of the weight gain of the heavy rare earth-free magnet matrix. The second-stage diffusion temperature is 800℃, and the second-stage diffusion time is 12 h.

[0095] Examples 5-9 describe a heavy rare earth-free grain boundary diffusion magnet prepared using the same method as in Example 5-1, except that the material of the second diffusion layer is PrAlCu, and the weight gain after drying is 5.0 wt% of the weight gain of the heavy rare earth-free magnet matrix. The second-stage diffusion temperature is 850℃, and the second-stage diffusion time is 12 h.

[0096] Examples 5-10: A heavy rare earth-free grain boundary diffusion magnet, prepared in the same way as in Example 5-1, except that the material of the second diffusion layer is PrAlCu, and the weight gain after drying is 4.5wt% of the weight gain of the heavy rare earth-free magnet matrix. The second-stage diffusion temperature is 700℃ and the second-stage diffusion time is 15h.

[0097] Examples 5-11: A heavy rare earth-free grain boundary diffusion magnet, prepared in the same way as in Example 5-1, except that the material of the second diffusion layer is PrAlCu, and the weight gain after drying is 4.5wt% of the weight gain of the heavy rare earth-free magnet matrix. The diffusion temperature is 800℃ and the diffusion time is 12h.

[0098] Examples 5-12 describe a heavy rare earth-free grain boundary diffusion magnet, prepared using the same method as in Example 5-1, except that the material of the second diffusion layer is PrAlCu, and after drying, the weight gain is 5.0 wt% of the heavy rare earth-free magnet matrix. The diffusion temperature is 800℃, and the diffusion time is 15 h.

[0099] Table 8. Performance of Heavy Rare Earth-Free Magnet Matrix Before and After Diffusion in Examples 5-1 to 5-6

[0100] As shown in Table 8, the HcJ increase can be precisely controlled based on the weight gain of the diffusion source and the second-stage diffusion temperature and time. Specifically, the control methods are as follows: when the weight gain is 0.5–2.0 wt%, the second-stage diffusion temperature is 800–950℃, and the diffusion time is 3–8 h, the HcJ increase is 0.5–2 kOe; when the weight gain is 2.0–4.0 wt%, the second-stage diffusion temperature is 700–900℃, and the diffusion time is 6–15 h, the HcJ increase is 2–4 kOe; and when the weight gain is preferably 4.0–5.0 wt%, the first-stage diffusion temperature is 900–950℃ for 0.5–1.5 h, the second-stage temperature is 700–850℃, and the diffusion time is 12–15 h, the HcJ increase is 4–5 kOe.

[0101] Example 6-1: A heavy rare earth-free grain boundary diffusion magnet, using a heavy rare earth-free magnet substrate N58 (14.85kGs + 12.98kOe), is prepared by conventional powder metallurgy. After slicing, the diffusion source is printed onto the product surface by printing method, and then placed in a vacuum sintering furnace for diffusion. The specific steps are as follows: The N58 matrix without heavy rare earth elements was prepared by a series of conventional powder metallurgy processes, including melting, crushing, air jet milling, pressing, and sintering. Thin sheets were obtained by wire cutting and ultrasonic cleaning.

[0102] Step 1: Diffusion source printing is performed. First, a TiCu alloy paste is printed on the thin film to form the first diffusion layer. The Ti and Cu elements in the TiCu alloy paste are 70 at and 30 at, respectively, with a weight gain of 0.5 wt% after drying. Then, a PrAlCu alloy paste is printed to form the second diffusion layer. The PrAlCu alloy paste has Pr, Al, and Cu elements in proportions of 82 wt%, 6 wt%, and 12 wt%, respectively. The paste is prepared from 80 wt% PrAlCu powder, 20 wt% terpineol, and 0.8 wt% PVB. After drying, the printed alloy paste has a weight gain of 1.08 wt%. The magnet is then placed in a vacuum sintering furnace for diffusion. The first stage temperature is 90°C for 1.0 h, and the second stage temperature is 800°C for 6 h. Aging is then performed at 500°C for 4 h to obtain magnet A.

[0103] Step 2: Cut magnet A into 7*6*2.25 pieces, remove the oxide layer on the surface with sandpaper, and then perform a magnetic performance test at 20℃±0.1℃ on a PFM.

[0104] Example 6-2: A heavy rare earth-free grain boundary diffusion magnet, prepared in the same way as in Example 6-1, except that the substrate is N54H (14.3kOe+18kGs), the material of the second diffusion layer is PrAlCu slurry, the weight gain after drying is 2.5wt% of the heavy rare earth-free magnet matrix, the diffusion temperature is 800℃, and the diffusion time is 10h.

[0105] Example 6-3: A grain boundary diffusion magnet without heavy rare earth elements, prepared in the same way as in Example 6-2, except that the substrate is N52H (14.15kOe + 18.1kGs), the material of the second diffusion layer is PrAlCu slurry, and the weight gain after drying is 2.2wt% of the heavy rare earth magnet matrix.

[0106] Example 6-4: A grain boundary diffusion magnet without heavy rare earth elements, prepared in the same way as in Example 6-1, except that the substrate is N48SH (13.8kOe + 20.5kGs), the material of the second diffusion layer is PrAlCu slurry, and the weight gain after drying is 1.10wt% of the matrix of the magnet without heavy rare earth elements.

[0107] Examples 6-5 describe a heavy rare earth-free grain boundary diffusion magnet, prepared using the same method as in Example 6-1, except that the substrate is N33SH (11.7kOe + 21.5kGs), the second diffusion layer is PrAlCu slurry, and after drying, the weight gain is 4.5wt% of the heavy rare earth-free magnet matrix. The diffusion temperature is 800℃, and the diffusion time is 12h.

[0108] Table 9. Remanence and intrinsic coercivity of Examples 6-1 to 6-5

[0109] As shown in Table 9, when the process described in this application is used to process different grades of heavy rare earth magnet substrates, the performance of the corresponding heavy rare earth magnet substrates can be improved. At the same time, sintering NdFeB magnets using high-grade heavy rare earth magnet substrates such as N50SH, N48SH, and N30UH results in lower cost and higher performance compared to conventional powder metallurgy heavy rare earth magnets.

[0110] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A heavy rare earth-free grain boundary diffusion magnet, characterized in that, The magnet comprises a heavy rare earth-free magnet matrix, a first diffusion layer covering the outer surface of the heavy rare earth-free magnet matrix from the inside out, and a second diffusion layer covering the outer surface of the first diffusion layer; the Ga content of the heavy rare earth-free magnet matrix is ​​not less than 0.2 wt%. The material of the first diffusion layer is Ti X Cu 1-X The material of the second diffusion layer is Pr. x Al y Co z Cu 1-x-y-z ; In the material of the first diffusion layer, X = 20 at% - 40 at% In the material of the second diffusion layer, x = 70wt%-90wt%, y = 0-9wt%, and z = 0-10wt%.

2. The heavy rare earth-free grain boundary diffusion magnet according to claim 1, characterized in that, In the first diffusion layer, X = 20 at%-30 at%; in the second diffusion layer, x = 80wt%-90wt%, y = 0-5wt%, z = 0-6wt%.

3. A method for preparing a heavy rare earth-free grain boundary diffusion magnet as described in any one of claims 1-2, characterized in that, Includes the following steps: Step 1: Cover the surface of the heavy rare earth magnet substrate with the material of the first diffusion layer, the weight gain of the covering is 0.1~0.5wt% of the heavy rare earth magnet substrate, and obtain magnet 1 covered with the first diffusion layer; Step 2: Cover the outer surface of magnet 1 with the material of the second diffusion layer, the weight gain of the covering is 0.5~5.0wt% of the weightless rare earth magnet matrix, to obtain magnet 2 covered with the second diffusion layer; Step 3: Perform grain boundary diffusion treatment on magnet 2. The grain boundary diffusion temperature is 700-1000℃ and the treatment time is 3.5-16.5h; the tempering temperature is 400-600℃ and the time is 3-6h to obtain a heavy rare earth-free grain boundary diffused magnet.

4. The method for preparing a heavy rare earth-free grain boundary diffusion magnet according to claim 3, characterized in that, In step three, the grain boundary diffusion treatment is divided into two stages: the first stage diffusion temperature is 850~1000℃ and the first stage diffusion time is 0.5~1.5h; the second stage diffusion temperature is 700~950℃ and the second stage diffusion time is 3~15h.

5. The method for preparing a heavy rare earth-free grain boundary diffusion magnet according to claim 4, characterized in that, In step two, the weight gain is 0.5wt~2.0wt%, the second-stage diffusion temperature is 800~950℃, and the second-stage diffusion time is 3~8h.

6. The method for preparing a heavy rare earth-free grain boundary diffusion magnet according to claim 4, characterized in that, In step two, the weight gain of the covering is 2.0wt%~4.0wt%, the second-stage diffusion temperature is 700~900℃, and the second-stage diffusion time is 6~15h.

7. The method for preparing a heavy rare earth-free grain boundary diffusion magnet according to claim 4, characterized in that, In step two, the weight gain of the covering is 4.0wt%~5.0wt%, the first-stage diffusion temperature is 900~950℃, and the first-stage diffusion time is 0.5~1.5h; the second-stage diffusion temperature is 700~850℃, and the second-stage diffusion time is 12~15h.

8. The method for preparing a heavy rare earth-free grain boundary diffusion magnet according to claim 3, characterized in that, In steps one and two, the method for covering the material of the first diffusion layer and the method for covering the material of the second diffusion layer are one of coating, magnetron sputtering, spraying, and screen printing.

9. The method for preparing a heavy rare earth-free grain boundary diffusion magnet according to claim 5, characterized in that, In steps one and two, the covering method is screen printing, and the material of the first diffusion layer or the material of the second diffusion layer consists of the following percentages of components: Solvent 18-20wt; first or second diffusion source powder 80wt; resin 0-2wt.